COST ANALYSIS OF THE EFFECT OF HOLDING PERIOD TRANSACTION ORDINARY SHARES IN JAKARTA STOCK EXCHANGE - Supardi, Supardi (Accounting, 2010)
" This research was conducted to determine whether transaction costs affect the holding period of shares of common stock of short-term on the Jakarta Stock Exchange. The samples were carried out adgement sampling of the most active stock and have the highest trading volume according to the JSX Monthly Statistics, the sample used in this study were 20 shares in JSE listed companies. Data used secondary data, while the method of data collection through the documentation and literature study method. The data analysis technique used is multiple regression analysis. Regression analysis shows that bid-ask spread in a single semester course which significantly affect the holding period of investors, while other variables are not significant. But basically the bid-ask spread, market value, and risk of return can be used to predict the variation of changes in the holding period for shares of common stock based on regression analysis of each independent variable affect the holding period, its just not significant" Keyword : Holding Period, BEJ